1953
DOI: 10.1111/j.1939-0025.1953.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications in therapy with adopted children.

Abstract: HE present study arose because it was our impression that a rather T I arge percentage of the children seen at the Hacker Clinic were adopted children, and that they as a group were extremely disturbed. Beyond the seriousness of their condition, they and their parents presented unusually difficult treatment problems. It was our intent to examine these cases as a group in order to determine what specific role, if any, the fact of the a d o p tion played in the etiology of the problems presented and in the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1960
1960
1988
1988

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…ALTHOUGH approximately 2 to 3.5% of children in the United States under age of 18 are adopted (22, 43), adopted children are referred for psychological treatment two to five times as frequently as their nonadopted peers. This finding has been replicated in such diverse countries as Great Britain, Israel, Poland, Sweden, and the United States (7, 9, 15, 19, 21, 29, 33, 38, 4244, 49, 51, 56, 57).…”
mentioning
confidence: 79%
“…ALTHOUGH approximately 2 to 3.5% of children in the United States under age of 18 are adopted (22, 43), adopted children are referred for psychological treatment two to five times as frequently as their nonadopted peers. This finding has been replicated in such diverse countries as Great Britain, Israel, Poland, Sweden, and the United States (7, 9, 15, 19, 21, 29, 33, 38, 4244, 49, 51, 56, 57).…”
mentioning
confidence: 79%
“…It should be noted, however, that in biological parent-child relationships, overprotectiveness has often been interpreted as a reactive formation to unconscious feelings of rejection toward the children. Eiduson and Livermore (1953) found that adoptive mothers of disturbed children often had problems providing firm limits on their adoptees' behavior because the situation touched on their repressed rejecting feelings. When the child retaliated angrily to discipline, the mother reneged.…”
Section: Theoretical Considerationsmentioning
confidence: 98%
“…A second line of evidence supporting the sentiment that traditional, closed adoption is a univocal, negative experience has been reinforced in the clinical literature primarily by members of the psychoanalytic community (7, 12, 20, 36, 51, 61, 7375, 84, 108, 119, 125, 147). Several analysts have acknowledged that adoption is often of great physical, psychological, and social value to all parties concerned (10, 58, 77, 149).…”
Section: Contemporary Literaturementioning
confidence: 99%